Sharing mobility solutions in remote touristic area: case study of Lithuania - Ušpalytė-Vitkūnienė, Rasa; Bureika, Gintautas; Burinskienė, Marija; Vabuolytė, Vaida; Skrickij, Viktor (Transport, 2022)
Sharing mobility solutions changes people’s lives in cities; however, such services are not common in remote areas, where the most widespread transport mode is a privately owned car. The main challenge is that the existing transport system fails to meet the population’s daily travel needs in such regions. Sharing mobility covers environmental issues, infrastructure development, digitalisation, integration of different transport modes, and people behaviour changes. This study analyses the possibility of expanding the existing urban mobility sharing system in remote tourist areas of Lithuania; for this purpose, a small resort in the central part of Lithuania – Birštonas was selected, and a survey of residents and tourists (visitors) was conducted. Using the survey results of residents and tourists, the needs for Car Sharing (CS) and micro-mobility services are determined. The attitude of municipality, residents, tourists, service providers towards micro mobility and vehicle sharing services is determined. Based on the achieved results, further steps of service development are proposed. The article’s main aim is to evaluate the views of various stakeholders on the development of micro mobility and CS systems in remote areas and propose development solutions.